2021
DOI: 10.1248/bpb.b21-00443
|View full text |Cite
|
Sign up to set email alerts
|

Salidroside Induces Apoptosis in Human Gastric Cancer Cells <i>via</i> the Downregulation of ENO1/PKM2/GLUT1 Expression

Abstract: Salidroside is reported to have a wide range of pharmacological properties and has been proven to play a key anti-cancer effect. This study investigated the effects of purified salidroside, an ingredient of Rhodiola rosea, on the proliferation of two human gastric cancer cell lines and further investigating its possible molecular mechanisms. We verified that salidroside exerts a dose-dependent inhibitory effect on the proliferation of SGC-7901 and MKN-45 human gastric cancer cells. Moreover, salidroside can in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Xiao et al (2018) showed that GLUT1 knockdown inhibits prostate cancer growth by suppressing tumor-cell glycolysis and proliferation while promoting cell cycle arrest. Similarly, other researchers reported that GLUT1 deficiency also inhibited CRC cell proliferation, migration, and glycolysis (Zhang et al, 2020b), while reversing the Warburg effect in gastric cancer cells, while enhancing cellular apoptosis (Dai et al, 2021). Dihydroartemisinin and rhodopsin are also reported to exert anticancer effects by inhibiting GLUT1 (Gao et al, 2020;.…”
Section: Glycolysis-targeted Cancer Therapymentioning
confidence: 84%
“…Xiao et al (2018) showed that GLUT1 knockdown inhibits prostate cancer growth by suppressing tumor-cell glycolysis and proliferation while promoting cell cycle arrest. Similarly, other researchers reported that GLUT1 deficiency also inhibited CRC cell proliferation, migration, and glycolysis (Zhang et al, 2020b), while reversing the Warburg effect in gastric cancer cells, while enhancing cellular apoptosis (Dai et al, 2021). Dihydroartemisinin and rhodopsin are also reported to exert anticancer effects by inhibiting GLUT1 (Gao et al, 2020;.…”
Section: Glycolysis-targeted Cancer Therapymentioning
confidence: 84%
“…Salidroside enhanced doxorubicine sensitivity of HeLa-ADR-luc cells through the regulation of PI3K/Akt/HIF-1α and doxorubicine-induced resistance pathways, and exerted cardioprotective activity [133]. Salidroside suppressed chronic myeloid leukemia cell proliferation and induces apoptosis by regulating the miR-140-5p/wnt5a/β-catenin axis [134], and induced apoptosis in human gastric cancer cells via the downregulation of ENO1/PKM2/GLUT1 expression [135].…”
Section: Anticancer Effects Of Rhodiola Rosea L and Its Main Constitu...mentioning
confidence: 99%
“…The main bioactive ingredient isolated from Rhodiola rosea is called salidroside, which was found to have a variety of biological properties such as anti-inflammation, anti-oxidation, anti-stress, and anti-cancer [ [167] , [168] , [169] , [170] , [171] ]. Bioactive components of Rhodiola rosea inhibited the degradation of p27 Kip1 via down-regulating the expression of PCNA, cyclin D1, and CDK4 in lung tissue of PH rat model induced by hypobaric hypoxia, which contributed to reduction of mPAP and RVHI [ 172 ].…”
Section: Traditional Chinese Medicine Monomers Inhibiting the Prolife...mentioning
confidence: 99%